Keterampilan Entrepreneurship Pada Guru Pendidikan Anak Usia Dini - Nurul Novitasari (Universitas Al-Hikmah Indonesia, 2019)
PAUD teacher not only teach of science to children, but to must have skills in entrepreneurship. Entrepreneurship can teach with education and training. Skills will be better if always trained for increase abbility, so become expert. While entrepreneurship is someone who thinks creative and innovative to create new and value-added products for mutual interests. To be a successful entrepreneur, the main requirement that must be possessed is having a spirit and temperament. One's soul and temperament are influenced by skill. (1) Basic skills; a. Leadership skills, b. Team motivating skills and building strong teams (team building), c. Team organizing skills, d. Conflict coping skills, e. Communication skills, f. Business strategy planning skills, g. Skills to overcome difficulties become opportunities. (2) Special skills; a. Selling skills, and b. Technical skills (for production). To grow entrepreneurship and increase entrepreneurial activities for PAUD teachers, it is very important to establish an entrepreneurship education and training for PAUD teachers. The following types of entrepreneurship skills training include: 1). Craft skills, 2). Skills in the form of service delivery, 3). Skills in the form of agrarian, such as: agriculture, plantation, pertganti, fishery, 4). Trading skills, 5). Food industry skills, 6). Skills in the field of household needs, 7). Skills for making light medicines.